Synthesis and fuel cell characterization of blend membranes from phenyl phosphine oxide containing flourinated novel polymers - KAYAMAN APOHAN, NİLHAN (ELSEVIER SCIENCE BV, 2014)
Novel fluorinated poly(arylene ether)'s are synthesized from polycondensation of bis (p-hydroxy-tetrafluoro) phenyl) phenyl phosphine oxide (PFPPO-OH) with 4,4'-dichlorodiphenyl sulfone (DCDPS) and 2,2-bis(4-hydroxyphenyl)propane (Bisfenol A) (Copolymer 1a) or 2,2-bis(4-hydroxyphenyl) hexafluoropropane (Bisphenol AF) (Copolymer lb). The fluorinated copolymers have been blended with sulphonated poly(ether ether ketone)-SPEEK by solvent casting method. The water uptake and proton conductivity of the blend membranes decreases with the increase of copolymer content as expected, but proton conductivity values are still comparable to that of Nafion117 (R) membrane. Addition of hydrophobic copolymer lb to the SPEEK caused increase in water vapor transmission. Methanol permeability of the membranes is decreased to 8.2 x 10(-8) cm(2) s(-1) and 1.3 x 10(-8) cm(2) s(-1) by addition of Copolymer la and lb, respectively and they are much lower than that of Nafion (R) 117 (1.21E-06 (cm(2) s(-1)). The blend membranes endure up to 6.5 h before it starts to dissolve. Hydrogen and oxygen permeability of the blend membranes is one-hundredth of the Nafion (R). Fluorinated polymer improved chemical, mechanical, and hydrolytic stability and also phenyl phosphine oxide structure in the ionomer increased the thermal stability, gas and methanol permeability and overcomed the drawbacks of the Naflon (R) type membranes. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Poly(arylene ether); Direct methanol fuel cell; Proton conductive membrane; Proton conductivity; PROTON-EXCHANGE MEMBRANES; POLY(ETHER ETHER KETONE); METHANOL PERMEABILITY; COMPOSITE MEMBRANES; HIGH-TEMPERATURE; ELECTROLYTE MEMBRANES; SULFONE) MEMBRANES; IONOMER MEMBRANES; ACID; COPOLYMERS